Small Intestinal Angioectasia: Characterization, Risk Factors, and Rebleeding. Issue 8 (September 2017) - Kaufman, Daniel; Leslie, Gregory; Marya, Neil; Han, Samuel; Gillespie, William; Holzwanger, Erik; Leslie, Richard; Cave, David
Abstract : Background: Gastrointestinal angioectasias (AEs) represent the most common vascular malformation within the gastrointestinal tract. This study sought to characterize epidemiologic/comorbid risk factors for AEs, rebleeding, and patterns of anatomic distribution within the small intestine. Study: This retrospective observational cohort study included 158 patients with AEs on capsule endoscopy (CE) from 2007 to 2015. Epidemiologic/comorbid data were collected and incorporated into final analysis. Each AE was categorized by location using a small bowel transit time-based quartile system. Rebleeding was evaluated following CE. Multivariate logistic regression was applied to statistically significant factors on univariate analysis to determine independent risk factors for rebleeding. Results: Most lesions were found in the first quartile (67.1%). Rebleeding occurred in 46 (29.7%) of the 156 patients for whom data were available. Rates of rebleeding were significantly higher among older patients (74.4 vs. 67.7 y, P =0.001), those with active bleeding on CE (41.3% vs. 16.5%, P =0.001), those with a history of aortic stenosis (21.7% vs. 9.2%, P =0.033), and those with AEs presents in quartile 3 (26.1% vs. 8.3%, P =0.003). Age, active bleeding on CE, and AE presence in quartile 3 were independently associated with rebleeding in multivariate analysis ( P =0.009, 0.023, and 0.008, respectively). Conclusions: These data help improve our knowledge of AEs regarding risk factors for rebleeding, and utilizes a novel small bowel transit time-based quartile localization method that may simplify future research and comparisons of anatomic distribution and behavior of small bowel AEs.